Remimazolam Anesthesia for Thyroid Surgery - Sae Nakagawa; Tomoharu Shakuo; Sakurako Matsudo; Hiroaki Soda; Kenji Shida (Case Reports in Anesthesiology)
Background. Critical upper airway obstruction, hematoma formation, and recurrent laryngeal nerve palsy have been reported as postoperative complications of thyroid surgery. Although remimazolam may reduce the risk of these complications, the efficacy of flumazenil with remimazolam has not been reported. We present the successful anesthesia management of thyroid surgery using remimazolam and flumazenil. Case Presentation. A 72-year-old woman was diagnosed with a goiter and scheduled for a partial thyroidectomy under general anesthesia. We used remimazolam for induction and maintenance using a neural integrity monitor, electromyogram, and endotracheal tube under the bispectral index monitor. At the end of the surgery, spontaneous respiration was confirmed after the intravenous administration of sugammadex, and the patient was extubated under mild sedation. In the operating room, we administered flumazenil intravenously to confirm recurrent laryngeal nerve palsy and active postoperative hemorrhage. The patient was confirmed to have no recurrent laryngeal nerve palsy under full wakefulness but developed active postoperative hemorrhage with normal blood pressure. The patient required reoperation and was reintubated under intravenous administration of propofol. The anesthesia was maintained using 5% of desflurane, and the patient was extubated without any postoperative problems. The anesthesia was then terminated. The patient had no recall of the procedure. Conclusion. Maintenance of general anesthesia using remimazolam allowed the use of a neurostimulator with minimal muscle-relaxant effects, and extubation under sedation reduced the risk of abrupt and unexpected changes in blood pressure, body movement, and coughing. Furthermore, after extubation, the patient was rendered fully awake using flumazenil to confirm the presence of recurrent laryngeal nerve palsy and active postoperative hemorrhage. In addition, the patient had no memory of the reoperation, suggesting that the anterograde amnesic effect of remimazolam had a favorable psychological outcome associated with the reoperation. We safely managed thyroid surgery using remimazolam and flumazenil.